The entrance examns to higher music education in Spain: meeting/disagreement point between teachers and students (Per Musi, 2021)
The teachers of the last cycle of Professional Clarinet Teaching must prepare the students to pass the Test for Access to Higher Education, while still meeting the specific requirements of the corresponding stage. Teachers and students face difficulties that may arise due to the complexity of the repertoire, technical complications derived from it, or psychological issues in public interpretation. The opinions of the agents involved are varied and lead, in many cases, to further stigmatize such evidence. In this document, the different considerations on the Entrance Exams by the professors of Professional and Higher Education, as well as the students, are collected, and it is intended to show a reality that, instead of leading to didactic rethinking more adjusted to the reality of the educational transition, have led to discussions focused on the level and talent of the students.